Investigations on thermal properties of CeO2/water nanofluids for heat transfer applications. (2021) - Michael Joseph Stalin, P.; Arjunan, T.V.; Matheswaran, M.M.; Manoj Kumar, P.; Sadanandam, N.
Abstract: At present, the nanofluids are being considered to be new emerging area of research which has lot of benefits in heat transport applications over traditional heat transport fluids. Since, nanofluids showcases an enhanced thermo-physical properties over the conventional fluids, they give better performance when compared with conventional working fluid. The current study evaluates the thermophysical properties of CeO2 /water nanofluids by experimentally by varying the temperature and volume concentrations. The volume concentration of CeO2 /water nanofluids is varied in five different values ranging from 0.01 to 0.3. The elemental composition of cerium oxide nanoparticles is analysed with the aid of EDX. The surface characteristics of the CeO2 nanoparticles are explored with scanning electron microscope. It is evaluated that thermal conductivity, co-efficient of viscosity and co-efficient of density of CeO2 /water nanofluids with 0.3 vol fractions have been increased by 35.97%, 1.76% % and 1.56% respectively when compared to that of 0.01 vol concentration. It has also been evaluated that specific heat of CeO2 /water nanofluids is decreased by 5% with 0.3 vol concentrations when compared to 0.01 vol concentrations.